Thematical 'Irfany exegesis of the Quran by Abu Al-Fadl Rashid al-Din al-Maybudi in Kasf al-Asrar Wa 'Uddat al-Abrar / Iman Kanani - Iman, Kanani (2017)
The book titled Kash al-Asrār wa ʿUddah al-Abrār (Revealing the Secrets and Preparations of the Righteous) is a Persian gnostic exegesis of the Qur’an containing many benefits. It has not been translated into any other language except English. Gnostic exegeses of Qur’an are limited with many being confused with Sufi exegeses or wayward Bāṭinī (allegoristic/esoteric) exegeses. The views concerning this approach to the interpretation of the Qur’an are largely negative. This study examines the gnostic trend in Kash al-Asrār wa ʿUddah al-Abrār based on an inductive, descriptive and analytical approach. In this regard, the researcher discusses and critiques associated with Gnosticism. It appeared that al-Maybudī adopted eight important themes: knowledge of God, fate and destiny, submission to the commands of Allah, the divine attributes, fear and hope, the help of God and His grace to people, God’s test of people in this world, the relationship with God, the remembrance and worship of God, humbling oneself in front of God, and seeking God’s pardon and forgiveness. Al-Maybudī used the letters (ḥurūf) as symbolic signals to the praise of God. He also derived the symbolism of the verses to illustrate God’s praise and holiness. Al-Maybudī also explains his gnostic terminology based on four foundations: the exoteric and esoteric, ordinal division, intellectual explanation, and scriptural explanation. He also linked the visual such as night and day, and the read, with symbolic meanings representing stages of Gnosticism of the human soul, his heart, or anything blessed, or pertaining to the relationship of the servant with his Creator. The study found that al-Maybudī developed his method of converting the Qur’anic verses to symbols indicative of spiritual experiences based on six approaches; associating the read text with Sufi principles and notions, deducing the esoteric from the exoteric verses, narrations, transforming the apparent meaning to spiritual meanings, deducing the symbolic meaning from the linguistic, transitioning from specific meanings to broad conceptual meanings, and by rendering the esoteric meaning the purpose of the exoteric meaning. Al-Maybudī also relied on the traditions of the Prophet (PBU), and the companions and righteous followers, great mystics, and Israeli anecdotes (al-Israililiyyāt). The characteristics of this exegesis is that al-Maybudī relied on authentic hadiths, embedding piety in the heart through praise and thanksgiving, seeking refuge, based on the doctrine of Ahl al-Sunnah wa al-Jamāʿah, focusing on tales and sermons in his gnostic approach, and a reliance on the ordinal divisions of religious concepts. However, he also used weak hadiths including some that were fabricated, and the transmission of strange Israeli anecdotes. He also mentions strange stories contrary to logic and Islamic law and offers symbolic interpretations that contradict scripture and sound intellect.